2017
DOI: 10.1111/poms.12675
|View full text |Cite
|
Sign up to set email alerts
|

Surprise, Anticipation, and Sequence Effects in the Design of Experiential Services

Abstract: T he most salient or peak aspect of a service experience often defines customer perceptions of the service. Across two studies, using the same novel form of a scenario-based experiment, we investigate the design of peak events in a service sequence by testing how anticipated and surprised peaks influence customer perceptions. Study 1 captures the immediate reactions of participants and Study 2 surveys participants a week later. In both studies, we find a main effect for the temporal peak placement, confirming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 93 publications
1
52
0
Order By: Relevance
“…As retrospective evaluations influence subjective experiences and eventually choice, both duration neglect and an overweighting of the peak and end moments have important real-world implications, for example, when helping people increase their longterm happiness (Wirtz, Kruger, Napa Scollon, & Diener, 2003) or when trying to improve consumer experiences (Cornil & Chandon, 2016;Dixon, Victorino, Kwortnik, & Verma, 2017). This raises the question of the extent to which the results obtained using aversive stimuli generalise to positive emotional experiences.…”
mentioning
confidence: 99%
“…As retrospective evaluations influence subjective experiences and eventually choice, both duration neglect and an overweighting of the peak and end moments have important real-world implications, for example, when helping people increase their longterm happiness (Wirtz, Kruger, Napa Scollon, & Diener, 2003) or when trying to improve consumer experiences (Cornil & Chandon, 2016;Dixon, Victorino, Kwortnik, & Verma, 2017). This raises the question of the extent to which the results obtained using aversive stimuli generalise to positive emotional experiences.…”
mentioning
confidence: 99%
“…MacInnis and Price (1990), for instance, have demonstrated that imagery processing stemming from anticipation has a direct positive effect on satisfaction. However, if consumer anticipation is encouraged, there is also a resulting risk that subsequent consumption may fail to meet expectations (Chan & Mukhopadhyay, 2010;Dixon, Victorino, Kwortnik, & Verma, 2017). Consumer satisfaction has long been explained through Expectancy Disconfirmation Theory [EDT], whereby (dis)satisfaction arises from discrepancy between expectations formed prior to consumption and the perceived product performance (Oliver, 1980;Oliver & Linda, 1981;Oliver & Winer, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Dixon et al. () investigated the impact that anticipation and surprise have on affect‐based design principles in the context of city‐tour planning. Collectively, this research suggests that behavioral‐design principles warrant additional research.…”
Section: Introductionmentioning
confidence: 99%
“…Second, planners may be faced with the task of combining events together to create bundles. Examples include academic conferences combining proposed presentations into tracks (Sampson, 2009); performing arts venues combining events into subscription packages (Dixon & Verma, 2013); music, art, and film festivals or museum exhibits combining elements (Martínez-de-Albéniz & Valdivia, 2018); cruise ship and city tours considering elements of an itinerary (Sun, Jiao, & Tian, 2011;Dixon, Victorino, Kwortnik, & Verma, 2017); and graduate management education considering topics and courses as parts of degree or certificate requirements. Bundle formation is often based on thematic characteristics of the events; for example, rival packages for sporting events, special interest tracks for conferences, genre-specific subscriptions for performing arts, packages in a film festival, and course requirements for a degree.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation